EFEKTIVITAS MODEL PEMBELAJARAN DARING MELALUI GOOGLE CLASSROOM PADA MATA PELAJARAN AL ISLAM DAN KEMUHAMMADIYAHAN DI SMK MUHAMMADIYAH 1 JATINOM KLATEN - Wulan Febriana Fitrianingrum; Zaenal Abidin; Nurul Latifatul Inayati (Universitas Muhammadiyah Surakarta, 2021)
This study aims to describe the learning process of Al-Islam and Kemuhammadiyahan using google classroom, measuring the effectiveness of using google classroom as a learning model and the constraints experienced in using google classroom. This research is a qualitative research and uses a phenomological approach to examine the effectiveness of using the Google Classroom application as a learning model. The research was conducted by taking the place and subject at SMK Muhammadiyah 1 Jatinom Klaten. Data collection was done by interview, observation and documentation. The results showed that 1) the online learning process using the google classroom application on Al-Islam and Kemuhammadiyahan subjects was carried out by taking notes, assignments and quizzes, 2) the effectiveness of using the google classroom application as an online learning model on Al-Islam and Kemuhammadiyahan subjects running. effectively and efficiently, 3) the obstacles in using google classroom in the online learning process are experienced by students and teachers. Student constraints: quotas, boredom and signals. Teacher constraints: demanded in online learning creativity. Solutions to overcome student problems: assignments are collected at school by using health protocols, giving quotas, and using school wifi. Solutions for teacher: holding reaining in using online learning aid applications.